Academic Writing: An Attempt to Demystify and Contextualize - Sharma, Prakash (The Harvest, 2025)
This paper attempts to demystify and contextualize academic writing by clarifying its major elements and showing how a conscious writer can easily consider them and write effectively. In our academia, the term 'academic writing' is made complicated by stuffing with jargons and equating it unnecessarily with complex writing. In contrast to these ideas, this paper unfolds the crucial components of academic writing and demonstrates how a potential writer can easily reflect on them and make writing impressive and effective. Following qualitative research design, this research obtains data from different scholarly publications to justify the claim. The paper concludes with the idea that academic writing is not a form of writing that is guided by the motive of complexity but it follows certain steps and communicates with the readers in a clear, logical and precise way. Moreover, this paper aims to correct the misconception of people toward academic writing and show how it is a process-based activity that demands conscious and careful attempts than ingenuity.